Electrochemical Study of Mixed-Ligand Complexes of In(III) with Succinic Acid and Serine - Moyal, Madhu; Gupta, O.D. (Asian Journal of Chemistry, 2010)
The composition and stability constants of complexes formed by In(III) with succinic acid and serine have been investigated in aqueous media. The sample complex of In(III) with L-serine was first investigated and formation constants evaluated by DeFord and Hume’s method and varified by Mihailov’s method. The value of formation constants were found to be log b11 =b12 = 9.94, log b21 = 5.63 at 298 K, calculated by Schaap and McMaster method. 4.72, log